FENOMENA KOMUNIKASI DALAM PERNIKAHAN BEDA AGAMA DI KOTA PEKANBARU - Mustaqimmah, Nurul; Wirman, Welly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Interreligous marriage is really happened in Pekanbaru, Riau. In phenomenonlogy perspective aiming to uncover the experience of intercultural communication marriage couple.The type of research was descriptive qualitative by an approach of phenomenology. Based on the fact the field through observation, deep interviews an documentation. The subject of research was a couple Interreligous marriage was of 3 couple in 3 – 5 year’s in married samples. The study focuses on exploring in communication experience of the sample. For this purpose of study proposed following three questions: (1) what is motive of Interreligous marriage’s couples? (2) How do this couples interpret the Interreligous marriage (3) How do they experience their marital communication with partner from different religion background.In the deep interview the informans give the personal experiences that contribute to the success of their marriage. Based on the analysis of data found three motives such as economic, love and affections, comfort feelings. Experience communication are pleasant communication experience and unpleasant communication experience.Keyword: marriage communication, Interreligous marriage, love, affections, comfort feelings, Experience communication